Penggunaan Gaya Bahasa Kiasan Novel Dalam Mihrab Cinta Karya Habiburrahman El Shirazy - Dasril, Reti; Atmazaki, Atmazaki; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study were (1) to descript style of shimile language that used in novel Dalam Mihrab Cinta by Habiburrahman El Shirazy, (2) to descript the style of shimile language which is more used in novel dalam Mihrab Cinta by Habiburrahman El Shirazy, (3) to descript the style of shimile language function in novel Dalam Mihrab Cinta by Habiburrahman El Shirazy. The data of this study are sentences inside of novel Dalam Mihrab Cinta by Habiburrahman El Shirazy. Which is used the style of shimile language. The data resource of this study is novel Dalam Mihrab Cinta by Habiburrahman El Shirazy. This data are collect by (1) read the novel repeatedly understanding the novel Dalam Mihrab Cinta by Habiburrahman El Shirazy , by the purpose ae to have the understanding clearly which is novel that had study, (2) write the sentences which have the style of shimile language which are match with teory of Gorys Keraf, and (4) put in the style of shimile language which had fomating into inventarritation data. Discovery of this study is the style of shimile language in this novel.